New Opportunities For Research Publication - McGinnis, Ronald (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Just as the Internet is transforming traditional teaching models in medical education, it also is changing the publication model for scholarly work as evidenced by the growth in open access journals no longer tied to the volume/issue cycles of traditional printing. Medical schools around the world are adopting this concept to facilitate publication resulting from early research involvement of students and the transition to academic medicine of residents and fellows.